Maisons paysannes d'un village d'Apamène, Serğilla (ive-vie siècles - Massif calcaire de la Syrie du Nord) - Duvette, Catherine; Charpentier, Gérard; Piaton, Claudine (Antiquité Tardive - Late Antiquity - Spätantike - Tarda Antichità, 2013)
Abstract The Limestone Massif of northern Syria constitute an extraordinary group of archaeological settlements. They include over 700 sites from the Roman and Byzantine periods in a wide region bordered by Turkey in the north, Apamea in the south, the Afrin and Oronte’s valleys in the west and the plain of Aleppo in the east. These sites are not only important for their profusion, but also for their rural nature. The recent and detailed study of the well preserved remains of one of these settlements, Serğilla, located in the ğebel Zāwiye, offered the opportunity to explore various aspects of the daily life of a rural community and its evolution between the 4th and the 6th centuries AD. Three houses among others, built during different phases of the development of the village, are emblematic of this evolution.